Ebola Virus VP40 Modulates Cell Cycle and Biogenesis of Extracellular Vesicles - Pleet, Michelle L (J Infect Dis, 2018)
BACKGROUND: Ebola virus (EBOV) mainly targets myeloid cells; however, extensive death of T cells is often observed in lethal infections. We have previously shown that EBOV VP40 in exosomes causes recipient immune cell death. METHODS: Using VP40-producing clones, we analyzed donor cell cycle, extracellular vesicle (EV) biogenesis, and recipient immune cell death. Transcription of cyclin D1 and nuclear localization of VP40 were examined via kinase and chromatin immunoprecipitation assays. Extracellular vesicle contents were characterized by mass spectrometry, cytokine array, and western blot. Biosafety level-4 facilities were used for wild-type Ebola virus infection studies. RESULTS: VP40 EVs induced apoptosis in recipient T cells and monocytes. VP40 clones were accelerated in growth due to cyclin D1 upregulation, and nuclear VP40 was found bound to the cyclin D1 promoter. Accelerated cell cycling was related to EV biogenesis, resulting in fewer but larger EVs. VP40 EV contents were enriched in ribonucleic acid-binding proteins and cytokines (interleukin-15, transforming growth factor-β1, and interferon-γ). Finally, EBOV-infected cell and animal EVs contained VP40, nucleoprotein, and glycoprotein. CONCLUSIONS: Nuclear VP40 upregulates cyclin D1 levels, resulting in dysregulated cell cycle and EV biogenesis. Packaging of cytokines and EBOV proteins into EVs from infected cells may be responsible for the decimation of immune cells during EBOV pathogenesis.